Changes in Prescribing Antithrombotic Therapy in Patients with Atrial Fibrillation in the Multidisciplinary Hospital in Volgograd from 2012 to 2020 - A. S. Gerasimenko; O. V. Shatalova; V. S. Gorbatenko; V. I. Petrov (Рациональная фармакотерапия в кардиологии)
Aim. To study the frequency of prescribing antithrombotic agents in patients with non-valvular atrial fibrillation (AF) in real clinical practice, to evaluate changes of prescriptions from 2012 till 2020.Material and methods. The medical records of inpatients (Form 003/y) with the diagnosis AF, hospitalized in the cardiological department were analyzed. According to the inclusion criteria, the patients were over 18 years of age, established diagnosis of non-valvular AF. There were two exclusion criteria: congenital and acquired valvular heart disease and prosthetic heart valves. In retrospective analysis we have included 263 case histories in 2012, 502 ones in 2016 and 524 in 2020. CHA2DS2-VASc score was used for individual stroke risk assessment in AF. The rational use of the antithrombotic therapy was evaluated according with current clinical practice guidelines at analyzing moment.Results. During period of observation the frequency of antiplatelet therapy significantly decreased from 25,5% to 5,5% (р<0.001), decreased the frequency of administration of warfarin from 71,9% to 18,3% (р<0.001). The frequency of use of direct oral anticoagulants increased in 2020 compared to 2016 (р<0.001). For patients with a high risk of stroke anticoagulant therapy was administered in 71.8% of cases in 2012, 88.5% in 2016 and 92.5% in 2020. Before discharge from hospital majority of patients (72%) achieved a desired minimum international normalized ratio (INR) from 2.0 to 3.0 in 2012. In 2016 and 2020 an only 33% and 40.6% of patients achieved INR (2.0-3.0).Conclusion. Doctors have become more committed to following clinical guidelines during the period of the investigation. In 2020 antithrombotic therapy for atrial fibrillation was suitable according to current clinical guidelines.